Polymorphisms of Vitamin D Signaling Pathway Genes and Calcium-Sensing Receptor Gene in respect to Survival of Hemodialysis Patients: A Prospective Observational Study - Alicja E. Grzegorzewska; Monika K. Świderska; Adrianna Mostowska; Wojciech Warchoł; Paweł P. Jagodziński (International Journal of Endocrinology)
We evaluated in the 7-year prospective study whether variants in vitamin D pathway genes and calcium-sensing receptor gene (CASR) are determinants of mortality in hemodialysis (HD) patients (n=532). HRM analysis was used for GC rs2298849, GC rs1155563, RXRA rs10776909, RXRA rs10881578, and CASR rs7652589 genotyping. GC rs7041, RXRA rs749759, VDR rs2228570, and VDR rs1544410 were genotyped using PCR-RFLP analysis. The minor allele in GC rs2298849 was associated with all-cause mortality in univariate analysis (HR 1.330, 95% CI 1.046–1.692, P=0.020). Bearers of the minor allele in GC rs2298849 demonstrated higher infection/neoplasm mortality than major allele homozygotes also in multivariate analysis (HR 2.116, 95% CI 1.096–4.087, P=0.026). Cardiovascular mortality was associated with major homozygosity (CC) in VDR rs2228570 (HR 1.896, 95% CI 1.163–3.091, P=0.010). CC genotype patients were more often dyslipidemic than TT genotype subjects (46.1% versus 31.9%, P=0.047). Dyslipidemics showed higher frequency of rs1544410_rs2228570 haplotype AC than nondyslipidemics (26 versus 18%, Pcorr=0.005), whereas TT genotype patients were at lower risk of dyslipidemia compared with CC/CT genotype patients (HR 0.59, 95% CI 0.37–0.96, P=0.04). In conclusion, GC rs2298849 and VDR rs2228570 SNPs are associated with survival on HD. VDR-related cardiovascular mortality may occur due to connections of rs2228570 with dyslipidemia.